Penatalaksanaan Fisioterapi Pada Syndrome Obstructive Post Tuberculosis (SOPT) Di RS Paru Dr Ario Wirawan - R0smawati, Ema Nur, Isnaini Herawati S. Fis, S.Pd, M.Sc (2015)
Background : Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Characterized by shortness of breath, pain, spasms, thoracic expansion limitations and functional limitations. Modalities are given to this condition infrared, massage, stretching, and diaphragm breathing nebulizer. Objective : To determine the benefits of infrared modalities, massage, stretching, nebulizer and diaphragm breathing in reducing pain, reducing spasms, reduce shortness of breath, increase thoracic expansion and improve functional activities. Methods : The method used physiotherapy in the case that the infrared modality, nebulizer and diaphragm breathing. The evaluation was done by the method of measurement of pain ( VAS ), spasm ( palpation ), breathlessness ( Borg Scale ), thoracic expansion ( midline ) and functional activity ( London Scale ). Results : After 6 times of therapy showed a decrease in tenderness T1 : 3.6 cm to T6 : 2.3 cm, a decrease in the level of T1 spasm spasm is becoming a mild spasm T6 level, a decrease in the degree of breathlessness T1 : 4 to T6 : 2, increase thoracic expansion in the axilla T1 : 1.5 cm to T6 : 2.9 cm, the intercostal 4 T1 : 1.7 cm to T6 : 2.7 cm, the lower costa ( procesus xypoideus ) T1 : 1.3 cm into T6 : 2.7 cm. Conclusion : in the case of infrared modalities, massage, stretching, and diaphragm breathing nebulizer can reduce pain, reduce spasms, reduce shortness of breath, increase thoracic expansion and improve functional activities.